Effect of positive psychology interventions on psychological well-being of midwives: A randomized clinical trial - Fatemeh Shaghaghi; Zahra Abedian; Mohammad Forouhar; Habibollah Esmaily; Elnaz Eskandarnia (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: The psychological well-being of midwives is very important in the context of providing health services to two vulnerable groups of society, namely, mothers and infants. Therefore, the present study was conducted aiming to investigate the effect of positive psychological interventions on the psychological well-being of midwives. MATERIALS AND METHODS: The present study was a randomized clinical trial with pretest-posttest design along with a control group. The statistical population of the study included all midwives working in community health centers of Mashhad City, Iran, which were first selected through cluster sampling method from five health centers of the city, i.e. centers 1 and 3. Then, all centers and subsidiary bases of these centers were listed, and the centers and bases were divided into two groups of intervention and control by simple random allocation method. Sixty respondents were randomly assigned to two equal intervention and control groups and responded to the Ryff's Psychological Well-being questionnaire in two stages of pretest and posttest. Educational interventions based on interventions, including Seligman's PERMA model, in which psychological well-being is defined in terms of five domains namely positive emotions (P), engagement (E), relationships (R), meaning (M), and accomplishment (A), were conducted in eight sessions of 2 h (two sessions per week). Data were analyzed using independent t-test, paired t-test, Mann-Whitney test, and Wilcoxon test. RESULTS: There was a significant difference between the posttest scores of the two intervention and control groups in the total psychological well-being variable (P < 0.001). CONCLUSION: Given the findings of the study, it is suggested to use the Seligman's PERMA model to improve the psychological well-being of midwives in health centers.